Human resource management a critical approach - Collings, David G.; Wood, G.; Szamosi, Leslie T. (Routledge, 2019)
Despite over three decades of debate around the nature of human resource management (HRM), its intellectual boundaries and its application in practice, the field continues to be dogged by a number of theoretical and practical limitations. Written by an international team of respected scholars, this updated textbook adopts a critical perspective to examine the core management function of HRM in all its complexity -- including its darker sides. Human Resource Management: A Critical Approach opens with a critique of the very concept of HRM, tracing its development over time, and then systematically analyses the context of HRM, practice of HRM and international perspectives on HRM. New chapters commissioned for this second edition look at HRM and the issues of diversity, migration, global supply chains and economic crisis. This textbook is essential reading for advanced and inquisitive students of HRM, and for HRM professionals looking to deepen their understanding of the complexities of their field